Molecular point-of-care testing technologies: Current status and challenges - Yanbing Zu; Hong Chang; Zhanfeng Cui (Nexus)
As molecular point-of-care testing (POCT) enables timely and accurate diagnosis, its importance is increasingly recognized and has been highlighted during the COVID-19 pandemic. Despite significant improvements in recent years, many technological challenges remain. There is still a gap between current methods and those needed for accurate molecular POCT ready to use under various conditions. Further development of novel molecular POCT technologies is essential for responding to present clinical diagnostics on infectious diseases as well as cancers, preparing for future pandemics, and allowing rapid genetic testing for personalized medicine. This review examines each key aspect of molecular POCT and gives a concise summary of the current status and advancements in sample collection and storage, nucleic acid extraction, DNA amplification, and signal generation and detection methods. We address the challenges hindering the smooth integration of molecular POCT into field and home settings, emphasizing the pressing need for innovative solutions to overcome these obstacles. Additionally, we explore regulatory requirements and the necessity to reduce the costs of goods aiming at applications in low- and middle-income countries. Throughout our discussion, we envision ways to improve molecular POCT methodologies and enhance their efficacy in diverse clinical and remote settings and in public health scenarios. We believe that the global expansion of molecular POCT will help advance the United Nations Sustainable Development Goals. Broader context: When patients visit a hospital, they typically undergo in vitro diagnostics, allowing doctors to evaluate their conditions before taking further action. Samples are sent to labs for testing, with results available in hours or even weeks, which can be unacceptable for those with acute illnesses. To address this issue, point-of-care testing (POCT) technologies have rapidly evolved, enabling on-site testing. During the COVID-19 pandemic, POCT played a crucial role in controlling the spread of the virus and has since gained significant attention. To effectively tackle current and future global health challenges, particularly in resource-limited countries, further advancements in POCT are critical. Molecular POCT, which relies on complex nucleic acid analysis, needs improvements in speed, convenience, and cost-effectiveness. Continuous innovation and the integration of multidisciplinary technologies will be essential. This review explores the scope of molecular POCT applications, necessary testing steps, current research progress, relevant regulatory standards, as well as the technical challenges involved. We also address the global scaling up of molecular POCT needed to support the United Nations Sustainable Development Goals.